Role of nitric oxide and endothelial NO synthase in carcinogenesis - V. P. Deryagina; N. I. Rizhova; L. A. Savluchinskaya; K. I. Kirsanov (Успехи молекулярной онкологии, 2021)
Introduction. Nitric oxide (NO) produced by NO synthases (NOS) is involved in the regulation of vital physiological functions. At the same time, NO and NOS are involved in events associated with the tumor process: mutagenesis, proliferation, apoptosis, angiogenesis, etc., exerting a multidirectional effect on the tumor.Objectives – analyze and summarize literature data concerning the role of NO and endothelial NOS (eNOS) in the initiation and progression of tumors, as well as in the inhibition of tumor growth.Materials and methods. In preparing the review, publications of information bases of biomedical literature were used: SciVerse Scopus (538), PubMed (1327), Web of Science (905), Russian Science Citation Index (125).Results. The molecular mechanisms of the action of NO and its derivatives on the initiation and progression of carcinogenesis have been explored. Numerous factors and conditions regulating the activity of eNOS in health and tumor growth have been analyzed. The molecular signaling pathways through which the pro-tumor effects of NO and eNOS, stimulating angiogenesis, lymphangiogenesis, are realized, including through the mobilization of stem cells, are considered.Conclusion. Nitric oxide produced by activated eNOS promotes tumor progression by increasing the proliferation of tumor cells, enhancing the action of pro-angiogenic factors, stimulating angiogenesis, lymphangiogenesis, and metastasis. Selective inhibition of increased eNOS activity may be a promising therapeutic approach aimed at reducing metastasis and tumor growth.